Penerapan Model Pembelajaran Team Games Tournament (TGT) dalam Meningkatkan Partisipasi Belajar Siswa (Studi Kegiatan Praktik Pengenalan Lingkungan Persekolahan di SMAN 6 Pandeglang) - Nela Avrilia Salsabila; Asih Selma Al Karamy; Siti Rohmah; Anisa Nurhasanah; Imas Mahliah; Ahmad Supena (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research focuses on the application of the Teams Games Tournament (TGT) learning model to enhance student participation at SMAN 6 Pandeglang. This topic is significant because many students exhibit low engagement in collaborative learning environments. TGT, as a cooperative model, involves students in competitive games that encourage their active involvement. The research employs a qualitative descriptive method, following five steps of TGT implementation: information delivery, team formation, games, tournaments, and group awards. The findings indicate that the application of the TGT model successfully improved student participation and motivation. Students reported feeling more engaged and enthusiastic during the learning process. In conclusion, the TGT model is effective not only in increasing student participation but also in fostering 21st-century skills such as collaboration and communication.